Neural metabolite changes in corpus striatum after rat multipotent mesenchymal stem cells transplanted in hemiparkinsonian rats by magnetic resonance spectroscopy. (1st December 2013) - Fu, Wenyu; Zheng, Zhijuan; Zhuang, Wenxin; Chen, Dandan; Wang, Xiaocui; Sun, Xihe; Wang, Xin
<x xml:space="preserve">Abstract</x> Objective: To investigate the biochemical changes in striatum after rat bone marrow mesenchymal stem cells (MSCs) were transplanted into hemiparkinsonian rats and to further confirm the therapeutic effects of rat MSCs for Parkinson's disease (PD). Methods: 5-bromo-2-deoxyuridine (BrdU)-labeled MSCs were transplanted into the corpus striatum of the 6-hydroxydopamine (6-OHDA)-injected side of six PD model rats. Before and 8 weeks after MSC transplantation, ethological changes in PD rats were assessed. The expression of tyrosine hydroxylase (TH) in substantia nigra (SN) and striatum were measured using immunohistochemical methods. The differentiation of MSCs was detected by double immunofluorescence techniques. The concentrations of neural metabolites of N-acetylaspartate (NAA), choline (Cho) and creatine (Cr) were measured by 1H-magnetic resonance spectroscopy (MRS). Relative concentrations of NAA/Cr and Cho/Cr were calculated. Results: The behavior of PD rats in rotarod tests improved, and there were statistical differences in TH-positive cells in SN and TH-positive terminals in striatum after the transplantation of BrdU-labeled MSCs. Transplanted MSCs differentiated into MAP-2-positive neurons. Especially compared with pre-MSC transplantation, the neural metabolite NAA/Cr ratio of the 6-OHDA-injected side of the striatum increased (P < 0.05) and the Cho/Cr ratio decreased (P < 0.05). Conclusion: MSCs transplantation apparently improves neuronal function in the striatum of PD rats.